An independent learning method for orthopaedic surgeons performing shoulder ultrasound to identify full-thickness tears of the rotator cuff. - Murphy, R; Daines, M; Carr, A; Rees, J (2013)
BACKGROUND: There is an evolving interest in shoulder ultrasound performed by orthopaedic surgeons as part of routine clinical assessment of the rotator cuff in a so-called one-stop clinic. This study investigated the accuracy of ultrasound assessment of rotator cuff integrity performed by orthopaedic surgeons without prior experience of ultrasound who were following our proposed learning protocol. METHODS: We studied four surgeons without previous experience with shoulder ultrasound and monitored their ability to evaluate rotator cuff integrity using ultrasound compared with findings at arthroscopy. The surgeons attended a formal training course and were taught a protocol to identify and size full-thickness tears of the rotator cuff. The surgeons performed preoperative scans on the day that patients underwent shoulder arthroscopy. This allowed the surgeons to receive same-day feedback with comparison of arthroscopic images and ultrasound images. RESULTS: One hundred and fifty-nine shoulders were scanned by the surgeons in the study. In the initial training period, surgeons who performed >100 scans demonstrated a sensitivity of 94% and a specificity of 88% (a positive predictive value of 79% and a negative predictive value of 97%) for the identification of a full-thickness tear and agreed with intraoperative sizing of the defect in 84% of the scans. In the later training period, the predictive values showed a sensitivity of 90% and a specificity of 97% (a positive predictive value of 95% and a negative predictive value of 94%) for the identification of a full-thickness tear and agreement with intraoperative sizing for 95% of the scans. CONCLUSIONS: The predictive values obtained in this study for the evaluation of rotator cuff integrity were comparable with published results from experienced radiologists. This study demonstrates the capacity of our proposed learning protocol to train surgeons without previous ultrasound experience to reliably evaluate rotator cuff integrity using ultrasound within fifty to 100 scans.